Evaluation of a portable gas chromatograph with photoionization detector under variations of VOC concentration, temperature, and relative humidity. Issue 4 (3rd April 2018) - Soo, Jhy-Charm; Lee, Eun Gyung; LeBouf, Ryan F.; Kashon, Michael L.; Chisholm, William; Harper, Martin
ABSTRACT: The objective of this present study was to evaluate the performance of a portable gas chromatograph-photoionization detector (GC-PID), under various test conditions to determine if it could be used in occupational settings. A mixture of 7 volatile organic compounds (VOCs)—acetone, ethylbenzene, methyl isobutyl ketone, toluene, m -xylene, p -xylene, and o -xylene—was selected because its components are commonly present in paint manufacturing industries. A full-factorial combination of 4 concentration levels (exposure scenarios) of VOC mixtures, 3 different temperatures (25°C, 30°C, and 35°C), and 3 relative humidities (RHs; 25%, 50%, and 75%) was conducted in a full-size controlled environmental chamber. Three repetitions were conducted for each test condition allowing for estimation of accuracy. Time-weighted average exposure data were collected using solid sorbent tubes (Anasorb 747, SKC Inc.) as the reference sampling medium. Calibration curves of Frog-4000 using the dry gases showed R 2 > 0.99 for all analytes except for toluene (R 2 = 0.97). Frog-4000 estimates within a test condition showed good consistency for the performance of repeated measurement. However, there was ∼41–64% reduction in the analysis of polar acetone with 75% RH relative to collection at 25% RH. Although Frog-4000 results correlated well with solid sorbent tubes (r = 0.808–0.993, except for toluene) most of the combinations regardless of analyte did not meet the <25% accuracy criterion recommended by NIOSH. The effect of chromatographic co-elution can be seen with m, p- xylene when the results are compared to the sorbent tube sampling technique with GC-flame ionization detector. The results indicated an effect of humidity on the quantification of the polar compounds that might be attributed to the pre-concentrator placed in the selected GC-PID. Further investigation may resolve the humidity effect on sorbent trap with micro GC pre-concentrator when water vapor is present. Although this instrument does not fulfill the accuracy criterion specified in the NIOSH technical report No. 2012–162, it can be used as a screening tool for range finding monitoring with dry gases calibration in the occupational setting rather than compliance monitoring.